Closing the Implementation Gap; Comment on "Insights Gained From a Re-analysis of Five Improvement Cases in Healthcare Integrating System Dynamics Into Action Research" - Sally Brailsford (Kerman University of Medical Sciences, 2023)
Holmström et al provide an interesting and thought-provoking contribution to a perennial problem: why, despite a vast number of applications of simulation modelling in healthcare over the past 70 years, there is still remarkably little evidence of successful implementation of model results. Their paper is a retrospective analysis of five case studies, all undertaken as consultancy, that used a blend of system dynamics (SD) modelling and action research (AR). This commentary assesses the effectiveness of this approach in achieving implementation, based on the evidence presented, and discusses some of the issues raised. These issues include a comparison of Holmström's approach with group model building (GMB) in SD, the differences between healthcare modelling projects undertaken by (a) business consultants and (b) academics, and the challenges of undertaking 'systematic' reviews of the grey literature.